Transplant-associated thrombotic microangiopathy - Tomasz Jarmoliński (Termedia Publishing House, 2021)
Transplant-associated thrombotic microangiopathy (TA-TMA), which is a severe and quite frequent complication of hematopoietic stem cell transplantation (HSCT) in children, significantly influences patients' overall survival. Endothelial damage plays a central role in pathogenesis and overactivation of complement resulting in high plasma concentration of C5b-9 acts as the key driver. The clinical picture consists of combination of nonimmunologic hemolytic anemia, thrombocytopenia and organ damage. The diagnosis, which is based on laboratory criteria, is difficult since they overlap symptoms of other HSCT complications: graft versus host disease, infections and drug toxicities. No efficacious treatment had been available till recent years when anti-complement therapy was introduced. Using of C5-blocking humanized antibodies eculizumab brought breakthrough improvement of 1-year post-transplant survival in high-risk TA-TMA which increased from 17 to 64%. To achieve optimal results the therapy should be modified according to pharmacokinetic and pharmacodynamic parameters. Other complement-targeted agents, ravulizumab and coversin, are currently being tested.